2019
DOI: 10.1016/j.rmed.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inspiratory muscle training on postural stability, pulmonary function and functional capacity in children with cystic fibrosis: A randomised controlled trial

Abstract: Background: Previous research has found conflictive results regarding the benefits of inspiratory muscle training (IMT) for cystic fibrosis (CF) patients. Also, involvement of postural stability is a rising concern in chronic lung diseases but its role in CF patients is poorly understood. Our aim was to investigate the effects of IMT in CF patients as well as analysing the factors which may be related to postural stability. Methods: Thirty-six children aged between 8 and 18 years with CF were randomly allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 37 publications
2
43
0
8
Order By: Relevance
“…There is an idea that the main respiratory muscles, which are also the deep core muscles, are important for balance. Therefore, effective training of the main respiratory muscle groups can improve balance, which has been supported by many studies (39,40). Lee's study showed that after breathing training, the diaphragm and transverse abdominis muscles were effectively activated in stroke patients, leading to a significant improvement in static seated balance, dynamic seated balance (8,41).…”
Section: Discussionmentioning
confidence: 87%
“…There is an idea that the main respiratory muscles, which are also the deep core muscles, are important for balance. Therefore, effective training of the main respiratory muscle groups can improve balance, which has been supported by many studies (39,40). Lee's study showed that after breathing training, the diaphragm and transverse abdominis muscles were effectively activated in stroke patients, leading to a significant improvement in static seated balance, dynamic seated balance (8,41).…”
Section: Discussionmentioning
confidence: 87%
“…These findings support the previous research and we think that similar mechanisms may have played a role. Although to the best of our knowledge there is no study investigating the effect of breathing VGE on balance, Zeren et al 42 found that MEP was an independent predictor for the overall LOST score in children with cystic fibrosis. The authors stated that the MEP is a parameter that reflects the abdominal muscle strength which plays an important role in providing dynamic balance.…”
Section: Discussionmentioning
confidence: 96%
“…The effects on the inspiratory muscles is considered particularly striking as greater lung insufflation is provoked, together with thoracic movement providing the body with increased stability. Similarly, outside the water, Zeren et al showed an increase in the Pi max and Pe max , during inspiratory muscle training, as an independent predictor for the limits of postural stability in children with chronic lung diseases, who increased their postural scores [ 36 ]. The inspiratory training in our study is facilitated by the pressure that the water generates on the chest of the patients, offering resistance to inspiration during movement in the water, necessary for the training of the involved muscles.…”
Section: Discussionmentioning
confidence: 99%